Waardenburg syndrome type II in a Chinese patient caused by a novel nonsense mutation in the SOX10 gene. (June 2016) - Ma, Jing; Zhang, Tie-Song; Lin, Ken; Sun, Hao; Jiang, Hong-Chao; Yang, Yan-Li; Low, Fan; Gao, Ying-Qin; Ruan, Biao
Abstract: Objective: Waardenburg syndrome is a congenital genetic disorder. It is the most common type of syndromic hearing impairment with highly genetic heterogeneity and proved to be related by 6 genes as follows: PAX3, MITF, SNAI2, EDN3, EDNRB and SOX10. This article aims to identify the genetic causes of a Chinese WS child patient. Methods: A Chinese WS child was collected for clinical data collection by questionnaire survey. DNA samples of proband and his parents were extracted from peripheral blood samples. Six candidate genes were sequenced by the Trusight One sequencing panel on the illumina NextSeq 500 platform. Results: A novel nonsense heterozygous mutation was found in the coding region of exon 2 in the SOX10 gene of proband. The novel nonsense heterozygous mutation could cause the replacement of the 55th lysine codon by stop codon (484T > C, C142R) and further more possibly cause terminating the protein translation in advance. However, both proband's parents had no mutation of genes above mentioned. Conclusion: The gene mutation of SOX10 [NM_006941.3 c.163A > T] is a novel nonsense mutation. No record of this mutation has been found in dbSNP, HGMD, 1000 Genomes Project, ClinVar and ESP6500 databases. It meets the condition of PS2 of strong evidence in 2015 ACMG Standards and Guidelines.